Song and speech: examining the link between singing talent and speech imitation ability - Christiner, Markus; Reiterer, Susanne M. (Frontiers in Psychology, 2013)
In previous research on speech imitation, musicality and an ability to sing were isolated as the strongest indicators of good pronunciation skills in foreign languages. We, therefore, wanted to take a closer look at the nature of the ability to sing, which shares a common ground with the ability to imitate speech. This study focuses on whether good singing performance predicts good speech imitation. Fourty-one singers of different levels of proficiency were selected for the study and their ability to sing, to imitate speech, their musical talent and working memory were tested. Results indicated that singing performance is a better indicator of the ability to imitate speech than the playing of a musical instrument. A multiple regression revealed that 64 % of the speech imitation score variance could be explained by working memory together with educational background and singing performance. A second multiple regression showed that 66 % of the speech imitation variance of completely unintelligible and unfamiliar language stimuli (Hindi) could be explained by working memory together with a singer’s sense of rhythm and quality of voice. This supports the idea that both vocal behaviors have a common grounding in terms of vocal and motor flexibility, ontogenetic and phylogenetic development, neural orchestration and sound memory with singing fitting better into the category of "speech" on the productive level and "music" on the acoustic level. As a result, good singers benefit from vocal and motor flexibility, productively and cognitively, in three ways. 1. Motor flexibility and the ability to sing improve language and musical function. 2. Good singers retain a certain plasticity and are open to new and unusual sound combinations during adulthood both perceptually and productively. 3. The ability to sing improves the memory span of the auditory short term memory.